2018
DOI: 10.21013/jmss.v10.n3.p3
|View full text |Cite
|
Sign up to set email alerts
|

Computing Academics into New Age Programs and Fields: Big Data Analytics & Data Sciences in Indian Academics—An Academic Investigation of Private Universities

Abstract: <p>India is moving towards a developed country and thus knowledge cultivation is very much required and in this context introducing new age programs and degrees are essential. This is required for the creation of next generation skills and knowledge as per industrial and organizational demands including Government etc. Data Science is about managing the large amount and complex data, moreover, it is also known as Big Data Technologies. Due to the wider requirement in different universities and organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…In a study by [10], an analysis of Data Science degree programs of 279 private universities in India revealed that 52 universities offer programs in Data Science at the undergraduate and Master's level. These Data Science programs are mainly part of Computer Technology departments and were offered within Engineering and Technology tracks [10].…”
Section: Undergraduate and Graduate Data Science Programsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study by [10], an analysis of Data Science degree programs of 279 private universities in India revealed that 52 universities offer programs in Data Science at the undergraduate and Master's level. These Data Science programs are mainly part of Computer Technology departments and were offered within Engineering and Technology tracks [10].…”
Section: Undergraduate and Graduate Data Science Programsmentioning
confidence: 99%
“…In a study by [10], an analysis of Data Science degree programs of 279 private universities in India revealed that 52 universities offer programs in Data Science at the undergraduate and Master's level. These Data Science programs are mainly part of Computer Technology departments and were offered within Engineering and Technology tracks [10]. In a study [3] where 42 undergraduate and Master's Data Science programs were analyzed, it was discovered that most of the programs were offered by joint departments and departments of computer science.…”
Section: Undergraduate and Graduate Data Science Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data science is an emerging academic field [1], which has its origins in Big Data and Cloud Computing and other complex science-related domains. Data Science is concerned with managing large and complex data and the use of data analytics technologies [1].…”
Section: Introductionmentioning
confidence: 99%
“…Data science is an emerging academic field [1], which has its origins in Big Data and Cloud Computing and other complex science-related domains. Data Science is concerned with managing large and complex data and the use of data analytics technologies [1]. The three pillars of data science are data, technology, and people, and the three critical areas of data science are analytics, infrastructure, and data curation [2].…”
Section: Introductionmentioning
confidence: 99%